A model of facilitative communication for the support of general hospital nurses nursing mentally ill people. Part I: background, problem statement and research methodology - Mavundla, T R; Poggenpoel, M; Gmeiner, A (Curationis (Pretoria), 2001)
The impressive growth in the extent and range of psychiatric services provided by general hospitals in South Africa creates stress among nurses employed in these settings who are not psychiatric trained. This manifests itself in negative attitudes displayed towards mentally ill people. The aim of this paper is to discuss the process followed in the development of the model of facilitative communication. A theory generative design was used. The research methods were dealt with in four steps of theory generation as set out below. Step 1 entailed concept analysis. This step was dealt with in two phases, namely concept identification and concept definition. During concept identification, a qualitative research strategy that is explorative, descriptive and contextual was used. This was achieved through field research conducted in an urban general hospital. A sample of twelve professional nurses was selected from a population of 800 professional nurses employed in a general hospital using the purposive sampling technique. This sample size was determined by saturation of data in themes. Both semi-structured individual phenomenological interviews and observations were used as methods of data collection. Giorgi's method of descriptive data analysis (1985) was used. Four themes emerged from the results of the study. The main concepts of the model were identified and classified using a survey list of Dickoff et al. (1968). Step 2 dealt with the creation of interrelationship statements between concepts identified in Step 1, while Step 3 dealt with the description of the model using strategies proposed by Chinn and Kramer (1991). In Step 4, the description of guidelines for operationalizing in practice was ensured. To ensure valid results, a model for trustworthiness proposed by Guba (Lincoln & Guba, 1985) was used. The following criteria for trustworthiness were applied in all the steps of theory generation: truth value, applicability, consistency and neutrality.